1975
DOI: 10.1021/jo00909a019
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of substituted 7,7,8,8-tetracyanoquinodimethanes

Abstract: Twenty-one 7,7,8,8-tetracyanoquinodimethanes substituted with Me, Et, i-Pr, F, CI, Br, I, OMe, OEt, 0-i-Pr, 0-i-Bu, O-i-C5H11, -O-CHzOCHr, SMe, and CN groups are reported along with several TCNQ dianion salts.T h e charge transfer complex between tetrathiofulvalene 3i, 3m, and 3n were prepared according to Scheme 11, startand tetracyanoquinodimethane (TTF-TCNQ) 1 shows high ing with p-xylenes 7 or terephthalic acids 8. T h e tere--. phthalic acids were converted first to their acid chlorides, then reduced to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(65 citation statements)
references
References 6 publications
1
62
0
2
Order By: Relevance
“…This system is of a great interest for material chemists because it plays the role of an electron acceptor in the formation of charge-transfer complexes. 19 The TCNQ-F4 -radical anion forms tight pairs in alkali metal salts such as [Na + /TCNQ-F4 -] or [K + /TCNQ-F4 -], even at room temperature. 20 In 1995 Sugimoto et al reported the first observation of weak ferromagnetism in purely organic radical solids such as [Li + /TCNQ-F4 -].…”
Section: Introductionmentioning
confidence: 99%
“…This system is of a great interest for material chemists because it plays the role of an electron acceptor in the formation of charge-transfer complexes. 19 The TCNQ-F4 -radical anion forms tight pairs in alkali metal salts such as [Na + /TCNQ-F4 -] or [K + /TCNQ-F4 -], even at room temperature. 20 In 1995 Sugimoto et al reported the first observation of weak ferromagnetism in purely organic radical solids such as [Li + /TCNQ-F4 -].…”
Section: Introductionmentioning
confidence: 99%
“…H13~ "~' 10 H14 BMT-TCNQ was prepared by a method analogous to the DuPont procedure in four steps starting from 1,4-bis(methylthio)benzene (Wheland & Martin, 1975). The dark brown powder was purified twice by vacuum sublimation using apparatus described previously (Mizuguchi, 1981).…”
Section: N3mentioning
confidence: 99%
“…37 However, this method involves the use of po-tassium or sodium cyanide and bromine for the preparation of cyanogen halide (which is again highly toxic), making the protocol environmentally unacceptable. Literature reports on various other methods for the preparation of cyanamide using different synthetic strategies, such as cyanation of amines using CN + equivalents as synthons, [38][39][40][41][42][43][44] Tiemann rearrangement of amidoximes, 45 coupling reactions involving Pd isocyanides, allyl carbonates and trimethylsilyl azide, 46 and sodium bis(trimethylsilyl)amide as deoxygenating or desulfurizing agents. 47 Yet another method for the preparation of cyanamides involves the reaction of hypervalent iodine(V) species with N,N 1 -disubstituted glycylamide.…”
Section: Introductionmentioning
confidence: 99%